Advancements and approaches in developing MXene-based hybrid composites for improved supercapacitor electrodes - Prasankumar T.; Manoharan K.; Farhana N.K.; Bashir S.; K. Ramesh; Ramesh S.; Ramachandaramurthy V.K. (Elsevier Ltd, 2025)
The rapid increase in population and widespread use of energy-consuming technologies are contributing to a substantial increase in the world's energy consumption. Supercapacitors have recently become a more desirable alternative due to their quick charging and discharging times, high power densities, and extended cycle lives. For many researchers, improving supercapacitor efficiency for multifunctional applications is a major area of study. Many elements have been employed as electrode materials to provide the best energy and power density while achieving the largest specific capacitance. Among these materials, 2D transition metal carbides and nitrides, commonly called MXenes, are emerging candidates, particularly in electrochemical energy storage applications. Because of their strength, flexibility, unique structure, increased electrical conductivity, large surface area, diversity of active sites, hydrophobicity, and hydrophilicity for cutting-edge energy storage technologies, MXenes are among the best active electrode materials. MXene, with its unique 2D layered structure, offers the infinite possibility of the intercalation of various capacitive materials. Also, MXenes have the properties of high hydrophilicity of metal oxides and high electrical conductivity of metals. Alongside, activated carbon (AC), graphene, carbon nanotubes (CNTs), transition metal oxides, and conducting polymers (CPs) act as excellent electrode materials owing to their outstanding thermal, mechanical, electrical, and morphological properties. According to recent studies, one of the perfect methods for energy storage applications is to integrate MXenes with other superior elements for generating MXene-based composite electrode materials. This review includes recent developments in the investigation of MXene-based hybrid composites for supercapacitors. It covers composite's synthesis strategies, electrode architecture, electrochemical performance, and their efficiency in supercapacitors. ? 2024 Elsevier Ltd